2021
DOI: 10.1016/j.fuproc.2020.106684
|View full text |Cite
|
Sign up to set email alerts
|

Review of pressurized chemical looping processes for power generation and chemical production with integrated CO2 capture

Abstract: Chemical looping has great potential for reducing the energy penalty and associated costs of CO2 capture from fossil fuel-based power and chemical production while maintaining high efficiency. However, pressurized operation is a prerequisite for maximizing energy efficiency in most proposed chemical looping configurations, introducing significant complexities related to system design, operation and scale-up. Understanding the effects of pressurization on chemical looping systems is therefore important for real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(25 citation statements)
references
References 155 publications
(256 reference statements)
0
15
0
Order By: Relevance
“…If we want to couple a CLC combustor with a gas turbine, we have to take into consideration that for the aims of the GTCLC_NEG process the kinetic triplets need to be derived at high pressure (with Pressurized TGA tests, see table 2). Pressurized Chemical Looping is well described in the recent review [54], many works presented in table 2 are taken from it. Table 2 reports only reduction tests performed at high pressure, while CSIC and TU Eindhoven and also CanmetEnergy have realized also oxidation tests in pressurized conditions [55,56].…”
Section: Detailed Kinetic Models Of Iron Reductionmentioning
confidence: 99%
“…If we want to couple a CLC combustor with a gas turbine, we have to take into consideration that for the aims of the GTCLC_NEG process the kinetic triplets need to be derived at high pressure (with Pressurized TGA tests, see table 2). Pressurized Chemical Looping is well described in the recent review [54], many works presented in table 2 are taken from it. Table 2 reports only reduction tests performed at high pressure, while CSIC and TU Eindhoven and also CanmetEnergy have realized also oxidation tests in pressurized conditions [55,56].…”
Section: Detailed Kinetic Models Of Iron Reductionmentioning
confidence: 99%
“…3d and e. Amini et al [80] have recently reviewed the effect of pressure in chemical looping system, concluding that high pressure is beneficial for the reaction kinetics and hydrogen production process. More review and discussion on the effect of reactor system configuration are addressed in Sect.…”
Section: Product Selectivity: Stoichiometry Thermodynamics and Kineticsmentioning
confidence: 99%
“…24,25 Although the CFB configuration has been demonstrated at the lab 26−28 and pilot 29−38 scales for several chemical looping processes, pressurizing this configuration (Figure 2a) could be difficult for this application considering that each reactor needs to be pressurized individually with the need for precise control of the circulation of the oxygen carriers to fulfill the heat and mass balances of the process; only a few studies are reported on pressurized chemical looping using the interconnected fluidized bed configuration. 39 The challenges magnify in threesteps processes such as CLPOX-H 2 , which would require three interconnected reactors with an oxygen carrier circulating between them. As a consequence, the studies on pressurized chemical looping operations are still very limited.…”
Section: Introductionmentioning
confidence: 99%
“…To maximize the economic and environmental benefits of CLPOX (or CLPOX-H 2 ), a pressurized operation is required to improve the overall process efficiency and simplify its integration with downstream GTL processes. Chemical looping-based processes have been investigated at larger scales using interconnected circulating fluidized beds (CFB). , Although the CFB configuration has been demonstrated at the lab and pilot scales for several chemical looping processes, pressurizing this configuration (Figure a) could be difficult for this application considering that each reactor needs to be pressurized individually with the need for precise control of the circulation of the oxygen carriers to fulfill the heat and mass balances of the process; only a few studies are reported on pressurized chemical looping using the interconnected fluidized bed configuration . The challenges magnify in three-steps processes such as CLPOX-H 2 , which would require three interconnected reactors with an oxygen carrier circulating between them.…”
Section: Introductionmentioning
confidence: 99%